2012
DOI: 10.1016/j.jprot.2012.07.015
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic identification of endothelial cell surface proteins isolated from the hepatic portal vein of mice infected with Schistosoma bovis

Abstract: Proteomic identification of endothelial cell surface proteins isolated from the hepatic portal vein of mice infected with Schistosoma bovis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…It is also worth mentioning that we failed to identify host plasminogen on the tegument despite the fact that this is an abundant plasma protein and that S. bovis can bind plasminogen on its surface [5]. Similarly, in other study in which we applied the same methodology to analyze the proteome of the endothelial surface of the portal vein of naïve mice and mice infected with S. bovis we also failed to detect plasminogen in spite of the presence of plasminogen receptors on the endothelial surface [24]. As a whole, these results seem to suggest that the method used in both studies would not be appropriate to capture and identify this protein.…”
Section: Accepted Manuscriptmentioning
confidence: 67%
See 3 more Smart Citations
“…It is also worth mentioning that we failed to identify host plasminogen on the tegument despite the fact that this is an abundant plasma protein and that S. bovis can bind plasminogen on its surface [5]. Similarly, in other study in which we applied the same methodology to analyze the proteome of the endothelial surface of the portal vein of naïve mice and mice infected with S. bovis we also failed to detect plasminogen in spite of the presence of plasminogen receptors on the endothelial surface [24]. As a whole, these results seem to suggest that the method used in both studies would not be appropriate to capture and identify this protein.…”
Section: Accepted Manuscriptmentioning
confidence: 67%
“…The method of vascular perfusion in vivo with sulfo-NHS-LC-biotin has been used in several disease models in order to establish an atlas of vascular proteins in health and disease [29][30][31][32][33]. More recently, we applied this methodology to study the proteome of the endothelial surface of the mouse portal vein, and we identified some of the changes induced in it after infection by S. bovis [24]. The present work is the first in which vascular perfusion has been used to investigate, in vivo, the proteins exposed by an intravascular pathogen on its surface to the host.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 2 more Smart Citations
“…However, we cannot ignore that the different protein extraction methods used in the current and previous research might account for the distinct protein libraries obtained, resulting in 8 other hypothetical proteins not being present in our LC-MS/MS data. Additionally, the level of expression of the remaining proteins on the spore surface might be too low to be detected, being masked by other much more abundant surface proteins (Arjunan et al 2009; de la Torre-Escudero et al 2012). Finally, the extracellular domains of the 8 putative proteins exposed on the spore surface likely cannot be biotinylated because they lack the ε-amine of lysine residues (de la Torre-Escudero et al 2012).…”
Section: Discussionmentioning
confidence: 99%